Integration of Musharakah Financing in The Development of MSMES in Developing Countries: Sharia and Sustainable Finance Perspectives - Ela, Nur; Rohmat Hidayat, Agus; Dwi Putri Pramesti, Ginna Novarianti (Institut Manajemen Wiyata Indonesia, 2025)
MSMEs (Micro, Small, and Medium Enterprises) play an essential role in the economies of developing countries. However, they often face difficulties in accessing financing that aligns with sustainable finance and Sharia principles. Musharakah financing, based on the principle of profit sharing, is an alternative that can support the development of MSMEs, particularly in developing countries that prioritize the Sharia economy. This research aims to analyze the integration of musharakah financing in the development of MSMEs in developing countries, as well as evaluate the benefits and challenges related to the application of sharia principles and sustainable finance in this context. This research employs a qualitative approach, utilizing case studies in several developing countries, including Indonesia and Malaysia. Data were collected through interviews with MSME actors, Islamic financial institutions, and relevant government agencies. The analysis was carried out by comparing musharakah financing practices in the MSME sector and their impact on business sustainability. The results of the research indicate that musharakah financing can enhance MSMEs' access to capital in a more equitable and sustainable manner. However, the main challenges include a lack of understanding of Sharia concepts and regulatory barriers that hinder optimal development. Musharakah financing has demonstrated the potential to stimulate local and global economic growth when supported by the right policies.